Histological and neuronal changes in the duodenum of hamsters infected with Leishmania (Leishmania) infantum - Cavallone, Italo N. [UNESP]; Lima, Sarah K.S. de [UNESP]; Oliveira, Karine S. [UNESP]; Passero, Luiz Felipe D. [UNESP]; Laurenti, Márcia D.; Jesus, Jéssica Adriana; Marinsek, Gabriela P. [UNESP]; Chucri, Thaís M. [UNESP]; Mari, Renata B. [UNESP] (Elsevier, 2022)
Visceral leishmaniasis is a neglected tropical disease caused by parasites belonging to the Leishmania genus that infect macrophages in different tissues such as the spleen, liver, lymph nodes, bone marrow, and intestine. Therefore, this study aimed to investigate the integrity of the intestinal tract and the nitrergic (NADPH-dp) and metabolically active (NADH-dp) myenteric neurons of the duodenum of golden hamsters infected with L. (L.) infantum. Therefore, thirty golden hamsters were divided into six groups (n = 5); three of them were infected with 2 × 107 promastigote forms of L. (L.) infantum by intraperitoneal route (Infected Group - IG) and three were inoculated with saline solution (control group - CG). After 30, 60 and 90 days post-infection (DPI) infected animals were euthanized and the liver, spleen and duodenum were collected to analyze tissue parasitism. The duodenum was processed using usual histological techniques to analyze the main changes that occurred during infection and histochemical techniques to phenotype myenteric neurons. Amastigote forms were observed in the spleen, liver, and duodenum during all experimental periods, and tissue parasitism in these organs increased significantly over time. At 30 DPI, reduction in muscle tunic, increase in the total intestinal wall and the number of goblet cells PAS+ was observed. At 60 DPI, an increase in intestinal crypts and intraepithelial lymphocytes was observed, and a reduction in intestinal villi was observed at 90 DPI, along with an increase in crypt size. Regarding neurons, an increase in the density of the NADPH-dp population was observed at 30 DPI, but at 60 and 90 DPI a significant reduction of this population was observed. In general, infection progression was observed to cause significant morphofunctional changes in the duodenum of infected hamsters.
Keywords: Intestinal wall; Leishmaniasis; Myenteric plexus